Comparative studies of two dimensional and three dimensional ultrasonic nuchal translucency in trisomy assessments - Lai K. Wee; Hum Y. Chai; Sharul R. Bin Samsury; Naizaithull F. Binti Mujamil; Eko Supriyanto (Anais da Academia Brasileira de Ciências, 2012)
Current two-dimensional (2D) ultrasonic marker measurements are inherent with intra- and inter-observer variability limitations. The objective of this paper is to investigate the performance of conventional 2D ultrasonic marker measurements and proposed programmable interactive three-dimensional (3D) marker evaluation. This is essentially important to analyze that the measurement on 3D volumetric measurement possesses higher impact and reproducibility vis-à-vis 2D measurement. Twenty three cases of prenatal ultrasound examination were obtained from collaborating hospital after Ethical Committee's approval. The measured 2D ultrasonic marker is Nuchal Translucency or commonly abbreviated as NT. Descriptive analysis of both 2D and 3D ultrasound measurement were calculated. Three trial measurements were taken for each method. Both data were tested with One-Sample Kolmogorov-Smirnov Test and results indicate that markers measurements were distributed normally with significant parametric values at 0.621 and 0.596 respectively. Computed mean and standard deviation for both measurement methods are 1.4495 ± 0.46490 (2D) and 1.3561 ± 0.50994 (3D). ANOVA test shows that computerized 3D measurements were found to be insignificantly different from the mean of conventional 2D at the significance level of 0.05. With Pearson's correlation coefficient value or R = 0.861, the result proves strong positive linear correlation between 2D and 3D ultrasonic measurements. Reproducibility and accuracy of 3D ultrasound in NT measurement was significantly increased compared with 2D B-mode ultrasound prenatal assessment. 3D reconstructed imaging has higher clinical values compare to 2D ultrasound images with less diagnostics information. As atuais medições bidimensionais (2D) com marcadores ultrassônicos com inerentes intra- e interobservadores têm limitações de variabilidade. O objetivo deste trabalho é investigar o desempenho de medições convencionais 2D com marcador ultrassom e uma proposta interativa tridimensional programável de avaliação com marcador (3D). Isto é essencialmente importante para analisar que a medição em 3D volumétrica possui maior impacto e medição de reprodutibilidade vis-à-vis a 2D. Vinte e três casos de ultrassonografia pré-natal foram obtidos do hospital que colaborou com a pesquisa após a aprovação pela Comissão de Ética. A medida do marcador 2D ultrassônica é Translucência Nucal ou comumente abreviado como NT. A análise descritiva de medição de ultrassom 2D e 3D foram calculados. Três medidas foram obtidas em ensaios para cada método. Ambos os dados foram testados com uma amostra de teste de Kolmogorov-Smirnov e os resultados indicam que as medições de marcadores foram distribuídos normalmente com significativos valores paramétricos de 0, 621 e 0, 596, respectivamente. A média e o desvio padrão para ambos os métodos de medição são 1, 4495 ± 0, 46490 (2D) e 1, 3561 ± 0, 50994 (3D).O teste ANOVA mostrou que medições computadorizadas 3D foram insignificantemente diferentes da média 2D convencional com nível de significância de 0, 05. Com coeficiente de correlação de Pearson com valor R = 0, 861, o resultado comprova forte correlação linear positiva entre medidas ultrassônicas 2D e 3D. Reprodutibilidade e exatidão do ultrassom 3D na medida da TN foram significativamente aumentadas em comparação com a avaliação ultrassom 2D na modalidade B-pré-natal. Imagem reconstruída em 3D tem maiores valores clínicos em comparção com as imagens de ultrassom 2D que possuem menos informações para diagnóstico.